DEVELOPMENT OF THE ACCOUNTING SYSTEM OF ACTIVITIES RESTAURANT TYPE (Modern information system and technologies, 2018)
In the article reviewed the methods Development of the accounting system of activities restaurant type. The purpose of the work is to develop a document management system for a company with a limited scope of functions, which will allow the user to conduct daily operations efficiently and conveniently. Development methods include studying the material, using object-oriented programming, working with databases MySQL.